Genetic Diversity of Juglans mandshurica Populations in Northeast China Based on SSR Markers - Zhang, Qinhui; Zhang, Xinxin; Yang, Yuchun; Xu, Lianfeng; Feng, Jian; Wang, Jingyuan; Tang, Yongsheng; Pei, Xiaona; Zhao, Xiyang (Frontiers in Plant Science, 2022)
Juglans mandshurica is a native tree species in northeast China. Due to habitat destruction and human disturbance, its population size has sharply decreased. Currently, information on molecular markers of J. mandshurica is limited and cannot meet the needs of germplasm resource evaluation and molecular marker-assisted breeding of J. mandshurica. Based on transcriptomic data from three tissues (leaves, bark and fruit pericarp), we developed expressed sequence tag simple sequence repeats (EST-SSRs) for J. mandshurica, and 15 polymorphic EST-SSR primers were initially selected. The average number of alleles (Na), expected heterozygosity (He) and polymorphic information content (PIC) at different loci were 18.27, 0.670, and 0.797, respectively. Population genetic diversity analysis revealed that the average Na, He and Shannon information indices (I) for 15 J. mandshurica populations were 6.993, 0.670 and 1.455, respectively. Among them, population Hunchun exhibited the highest genetic diversity (Na=7.933, He=0.723, I=1.617), while population Heihe exhibited the lowest genetic diversity (Na=4.200, He=0.605, I=1.158). STRUCTURE analysis, neighbor-joining method cluster analysis and principal coordinate analysis showed that the 343 individuals of J. mandshurica from 15 populations were clustered into three categories. Category 1 (green) had 147 individuals from 8 populations in Qingyuan, Caohekou, Jian, Ningan, Yongji, Baishishan, Helong and Maoershan; category 2 (blue) had 81 individuals from 3 populations in Hulin, Boli and Sanchazi; category 3 (red) had 115 individuals from 4 populations in Heihe, Hunchun, Fangzheng and Liangshui. Analysis of molecular variance (AMOVA) showed that genetic variations among and within individuals accounted for 16.22% and 21.10% of the total genetic variation, indicating that genetic variations within populations were greater than genetic variations among populations. The average genetic differentiation coefficient (Fst) and gene flow (Nm) between different populations were 0.109 and 4.063, respectively, implying moderate levels of genetic differentiation and gene flow. Based on the genetic diversity characteristics of different populations, we proposed various genetic conservation strategies for J. mandshurica.